Study on the mechanical properties of multi jet fusion 3D printed PA12 lattice structures - Lee, Jacob Yong Jin (Nanyang Technological University, 2023)
Multi Jet Fusion (MJF) is an Additive Manufacturing (AM) method introduced by HP Inc. in 2016. Despite its relatively young age in the AM industry, MJF has quickly grown and progressed to become a popular choice among many large industrial users in manufacturing products. MJF falls under the Powder Bed Fusion (PBF) category of AM. Other methods under PBF include Selective Laser Sintering (SLS) and High-Speed Sintering (HSS). Similarities between these manufacturing methods include the use of a heated chamber in which powder material is fused without the need for support. However, MJF and HSS use inkjet-dispensed agents and a heating element while SLS fuses the powder material through the use of a directed laser beam. Products manufactured by MJF feature a good surface finish, good feature resolution, and consistent mechanical properties, making them appealing to consumers. In this project, the mechanical properties of 4 MJF printed Polyamide 12 (PA12) lattice structures were investigated. The 4 lattice structures include 1 with straight walls, 1 with straight S-shaped walls, and 2 cuttlebone structures with varying wall curve amplitudes. Compression tests were conducted to obtain the experimental mechanical properties of the various lattice structures. Finite Element Analysis (FEA) was also conducted, and the obtained results were compared against the experimental values to identify trends or similarities. The results showed that the cuttlebone structure with the larger amplitude yielded the highest maximum load before failure and energy absorbed per unit volume, while the straight wall structure performed the weakest, with the lowest values observed for both the maximum load and energy absorbed.